FINITE NILSEMIGROUPS WITH MODULAR CONGRUENCE LATTICES - Alexander L. Popovich (Ural Mathematical Journal, 2017)
This paper continues the joint work [2] of the author with P. Jones. We describe all finitely generated nilsemigroups with modular congruence lattices: there are 91 countable series of such semigroups. For finitely generated nilsemigroups a simple algorithmic test to the congruence modularity is obtained.